Giving a lot of ourselves: How mother leaders in higher education experienced parenting and leading during the COVID-19 pandemic - Boche, Laura (Frontiers in Education, 2022)
This qualitative interpretative phenomenological analysis explored the lived experience of mother executive administrators in higher education during the COVID-19 pandemic. Utilizing the philosophical underpinnings of the Heideggerian phenomenological approach, the following research question guided this study: What are the lived experiences of mother executive administrators in higher education during the COVID-19 pandemic? Participants included nine self-identified mother executive administrators from one Midwest state at a variety of institution types and locations within the state. Data collection involved two focus groups and individual interviews with all nine participants. After data analysis, three recurrent themes emerged from the data: (1) Burnout and Exhaustion, (2) Never Enough: Responsibility Generated Feelings of Guilt, and (3) Receiving Support: Importance of Gender, Family Role, and Agency. The findings of this study exposed the neoliberal feminist and capitalistic ideological stronghold on the United States workforce and culture intensifying the already existing challenges of these mothers during the COVID-19 pandemic.